Skolēnu lasītprasmes pilnveide 2.klasē - Bicāne, Laura (Latvijas Universitāte, 2013)
The goal of Lauras Bicane’s diploma paper„Improvement of pupils’ reading skills in Grade 2” is to establish how regular reading of literature influences pupils’ quality of reading skills in Grade 2. This paper describesreading skills, key quality parameters of reading skills, analyzes developmentof primaryschool children.Practicalpart of this paper researcheslevelof the reading skillsin Grade 2 and analyzes experimental teaching activities for improvement of pupils’reading skills. Methods used in the research: research and analysis of pedagogical and psychological literature, questionnaire, data analysis, experimental pedagogical work. Thediplomapaper consists of60 pages,introduction, three chapters, conclusion, bibliography of 30 units, 6appendixes, 2 tables and 23pictures. Key words: reading skills, reading and quality.
Improvement of pupils’ reading skills in Grade 2
Keywords: Pedagoģija